Serial changes of I-123 FP-CIT SPECT binding asymmetry in Parkinson's disease: Analysis of the PPMI data - Jeong, Eun Hye; Sunwoo, Mun Kyung; Lee, Jae Yong; Han, Sun-Ku; Hyung, Sung Wook; Song, Yoo Sung (Frontiers in Neurology, 2022)
Background: Dopaminergic denervation and motor symptoms are usually asymmetric at the onset of Parkinson's disease (PD). In this study, we estimated the asymmetry of specific binding ratio (SBR) of I-123 FP-CIT SPECT images during 4-years of follow up, to demonstrate the pattern of serial changes of asymmetry. Methods: Clinical and I-123 FP-CIT SPECT image data of 301 PD patients and 141 normal controls were reviewed from the Parkinson's Progression Markers Initiative cohort. I-123 FP-CIT SPECT images were taken at baseline, 1-year, 2-year, and 4-year follow up periods for PD patients, and at baseline for normal controls. Asymmetry index were calculated by two methods. Method 1, by using the ratio of absolute difference of right and left SBRs to the average SBR. Method 2, by using the ratio of absolute difference of right and left SBRs to the SBR values of age-matched normal controls. Results: Asymmetry index by method 2 revealed a more significant decrease during the 4-year follow up period, compared with method 1. The baseline asymmetry index of the putamen by method 2 showed significant correlation with the nondominant putamen SBRs. However, there were no significant correlation with the baseline asymmetry index by method 2 and motor symptoms, cognition, nor autonomic symptoms. Conclusion: We suggest a novel asymmetry index in association to age-matched normal SBR values. This novel index could be adopted in predicting and evaluating the natural course of PD.